Application of the nursing process in the construction of the Nursing Care Systematization (SAE) to a patient with Marfan syndrome associated with aortic dissecting aneurysm: Experience report (Research, Society and Development, 2022)
Objective: Report the experience lived during the care provided by nurses to a patient with Marfan Syndrome (MS) in the context of cardiological emergency associated with dissecting aortic aneurysm. Case detailing: The present study into the type of experience report, qualitive, exploratory, analytical, descriptive which is based on the experience of nursing team professionals who provided assistance during the second half of 2020 to a patient with MS, with type I A aortic dissecting aneurysm, admitted to the referral hospital for cardiovascular assistance through the urgency and emergency cardiology service. From the initial clinical Picture, the Nursing Care Systematization (NCS) process was established. Final considerations: The experience showed the high relevance of the implementation of Nursing Care Systematization, with a focus on the Nursing Process (NP), in the treatment of clientes affected by MS, as well as the contribution of this article to the training of nursing professionals.